Beetroot and Sodium Nitrate Ameliorate Cardiometabolic Changes in Diet‐Induced Obese Hypertensive Rats. Issue 12 (14th November 2017) - Bhaswant, Maharshi; Brown, Lindsay; McAinch, Andrew J.; Mathai, Michael L.
Abstract : Scope: Dietary intake of beetroot by humans reduces blood pressure but whether this is caused by nitrate or betanin is not well‐defined; neither are effects on other signs of metabolic syndrome. Methods and results: Rats fed a high‐carbohydrate, high‐fat diet (H) for 16 weeks developed abdominal obesity, hypertension, altered cardiovascular and liver structure and function, and impaired glucose tolerance compared to rats fed a corn starch diet (C). H rats treated with ∼16 mg/kg/day of nitrate either from beetroot juice (H+B) or sodium nitrate (H+N) for the last 8 weeks reduced systolic blood pressure by ∼25 mmHg, improved cardiac structure and function, plasma lipid profile and plasma markers of liver function, reduced inflammatory cell infiltration in heart and liver and decreased left ventricular fibrosis. In the left ventricle, H rats increased mRNA expression of connective tissue growth factor (CTGF), monocyte chemoattractant protein 1 (MCP‐1), matrix metalloproteinase‐2 (MMP‐2), and adenosine monophosphate‐activated protein kinase‐alpha (AMPK‐α) and decreased mRNA expression of peroxisome proliferator‐activated receptor‐alpha (PPAR‐α); both beetroot and sodium nitrate diet‐fed rats decreased CTGF threefold, MCP‐1, and MMP‐2 twofold, and doubled PPAR‐α mRNA expression in left ventricular tissue. Conclusion: The similar functional and molecular responses to beetroot and sodium nitrate indicate that the nitrate content of beetroot reduced inflammation and improved cardiovascular, liver, and metabolic function in rats with metabolic syndrome, rather than betanin. Abstract : Rats fed a diet high in fat and carbohydrate developed cardiometabolic disorders. Beetroot juice, which is a rich source of nitrate, reversed the diet‐induced symptoms of metabolic syndrome in rats. Treatment of the rats with an equivalent dose of sodium nitrate to that contained in the juice replicated the beneficial effects of beetroot. The mechanisms underpinning the beneficial effects are likely to include prevention of infiltration of inflammatory cells to metabolic tissues including the heart and liver, as well as activation of anti‐fibrotic gene expresssion.